USQ: An E-university For An E-world - Taylor, James C.; Swannell, Peter (International Review of Research in Open and Distributed Learning, 2001)
The rapid rate of technological change and the rapidly growing number of institutions now embarking on Internet-based delivery means that more institutions are involved in distance education than at any other time in history. As institutions throughout the world increasingly offer courses via the Internet, there will emerge a global higher education economy in which institutions will face global competition for students, especially those involved in continuing professional education and lifelong learning. The emergence of the global higher education economy could well act as a catalyst for overcoming the institutional inertia that typifies the organisational culture of many universities. This transition from the Industrial to the Information Age was encapsulated by Dolence and Norris (1995), who argued that to survive organisations would need to change from rigid, formula driven entities to organisations that were "fast, flexible, and fluid" (p. 31) -- adjectives not typically used to describe the salient features of universities! This case study outlines the response of a well-established dual mode institution, The University of Southern Queensland (USQ), to the "gales of creative destruction" (Schumpeter, 1950, p. 84) that currently beset higher education institutions throughout the world.